Contesting the Esoteric Label of Sufism through Reformism and Orientalism - Syarifah, Mahda; Nurfadilah, Yustira (An-Nur International Journal of Islamic Thought, 2024)
This article explores how Sufism came to be commonly identified as Islamic esotericism within academic discourse and broader cultural understandings. Drawing upon theoretical contributions from Wouter Hanegraaff and Kocku von Stuckrad, the study analyzes how Western intellectual movements—such as Orientalism, Romanticism, and Transcendentalism—framed Sufism through esoteric and mystical lenses, often severed from its Islamic roots. It also investigates how Islamic reformers like al-Afghānī, ʻAbduh, and Riḍā critiqued Sufism as irrational, superstitious, or obstructive to progress, paralleling Protestant criticisms of Christian mysticism. Methodologically, the study integrates discourse analysis, historical hermeneutics, and comparative textual analysis to trace the evolution of these narratives. Results show that classical Sufi orders such as the Naqshbandiyyah and Mevleviyya employed esoteric rhetoric without necessarily opposing orthodoxy. In modern contexts, Sufi expressions vary widely—from inward mystical cultivation (e.g., Naqshbandi-Haqqani) to outward political activism (e.g., Naqshbandi Army). These developments highlight Sufism’s role in contesting extremist ideologies and adapting to urban modernity. The article concludes that identifying Sufism solely as Islamic esotericism obscures its internal diversity and historical significance. Rather than treating it as a fixed category, scholars should engage with Sufism as a dynamic tradition deeply embedded in Islamic thought and practice, shaped by internal theological debates and external cultural forces.